The Influence Of Price, Customer Reviews And Brand Ambassadors On Purchase Decisions At The Kahf Official Shop Online Store On The Shopee Marketplace - Wachid, Arif; Sarwani, Sarwani; Listyawati, Liling (International Journal of Business and Quality Research, 2026)
This research is focused on assessing the extent to which prices, customer reviews, and the role of brand ambassadors affect consumer purchase decisions at Kahf Official Shop operating on the Shopee marketplace. The increasingly competitive dynamics of e-commerce competition encourage brands to have a deep understanding of the determinants of consumer behavior, especially in the men's personal care product segment. The price aspect is analyzed based on the level of affordability and suitability of the benefits received by consumers, while customer reviews are examined through indicators of source credibility, review quantity, and product rating assessment. On the other hand, the brand ambassador variable is measured through image strength, the level of relevance to the product, and consumer trust in the figure that represents the brand. This study uses a quantitative approach with data collection techniques in the form of surveys to Kahf consumers on the Shopee platform. Data processing and analysis were carried out using multiple linear regression methods to determine the influence of each independent variable on purchasing decisions. The results of the study are expected to provide empirical support that pricing, customer reviews, and brand ambassadors contribute significantly, both individually and simultaneously, in shaping consumer purchasing decisions. In addition, the findings of this research are expected to be the basis for strategic recommendations for Kahf in optimizing digital marketing through competitive pricing strategies, effective management of customer reviews, and the selection of brand ambassadors that are in accordance with the brand character.